THE EFFECTIVENESS OF USING E-LEARNING MOODLE FOR HOMEWORK IN IMPROVING READING ABILITY OF GRADE X STUDENTS OF SMAN 4 PADANG - Etry Suwandi; Refnaldi Refnaldi; Havid Ardi (Journal of English Language Teaching, 2013)
AbstractThis study aimed to examine the effectiveness of using e-learning Moodle for homework in improving reading ability of grade X students of SMAN 4 Padang. The study was an experimental research with the population grade X of SMAN 4 Padang in academic year 2012/2013. Sample is class X7 as the experimental group and class X10 as the control group. Post-test was given after treatment in the experimental class. The reading comprehension data of both groups were analyzed using t-test formula. T-test result of the study is 2,833, while the table-t is 1.999. Based on the result of the calculation, it can be concluded that the use of e-learning Moodle for homework is more effective in improving students' reading ability.AbstrakPenelitian ini bertujuan untuk melihat keefektifan penggunaan e-learning Moodle untuk pekerjaan rumah terhadap kemampuan membaca siswa di kelas X SMAN 4 Padang. Jenis penelitian ini adalah eksperimen dengan populasi penelitian siswa kelas X SMAN 4 Padang tahun ajaran 2012/2013. Sampelnya yaitu kelas X7 sebagai kelas eksperimen dan X10 sebagai kelas kontrol. Pos-tes diberikan setelah perlakuan pada kelas eksperimen. Data berupa nilai tes pemahaman membaca oleh kedua kelompok sampel dianalisis menggunakan rumus uji-t. Hasil uji-t penelitian adalah 2,833 sedangkan tabel-t adalah 1,999. Berdasarkan hasil penghitungan ini, disimpulkan bahwa penggunaan e-learning Moodle untuk pekerjaan rumah lebih efektif dalam meningkatkan kemampuan membaca siswa.Key words: reading ability, homework, E-learning Moodle